Language and Communication - Fauziah Nasution; Elissa Evawani Tambunan (IJCS: International Journal of Community Service, 2022)
Language as a communication tool has an important role in human interaction. Language can be used by humans to convey their ideas, ideas, desires, feelings and experiences to others. Language is a form of embodiment of human civilization and culture, in the linguistic dictionary, language is an arbitrary sound symbol unit used by a member of society to work together, interact and identify themselves. The spoken language between one region and another is different which is called a dialect. In order to unite the language in the community from several regions, a national language is needed. In addition, in the process of communication, speech acts also occur. A communication process cannot be separated from speech acts or speech events. The importance of communication encourages people to be more creative in creating new media as a means to facilitate the communication process.